2020
DOI: 10.1016/j.ijms.2019.116275
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Chemical Ionisation study of selected Volatile Organic Compounds (VOCs) by Ion Mobility Spectrometry coupled with orthogonal acceleration Time Of Flight Mass Spectrometry

Abstract: In this work we present an Atmospheric Pressure Chemical Ionisation (APCI) study of several organic solvents (methanol, ethanol, propan-2-ol, acetone, ethyl acetate, diethylamine) using the Ion Mobility Spectrometry (IMS) combined with the orthogonal acceleration Time Of Flight Mass Spectrometry (IMS-oaTOF MS). The ions were formed in interactions of the Reactant Ions (RI -H + .(H2O)3,4) with the studied volatile organic compounds (VOC's). The ions were analysed by IMS and in by IMS-oaTOF to assign ions accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The IMS-oaTOF MS instrument was described in detail elsewhere. ,, This instrument is equipped with an identical ion source and IMS drift tube as the standalone IMS. The ions, after passing the drift tube, penetrate through the 100 μm pinhole in the ion collector to the first chamber of a differential pumping interface.…”
Section: Methodsmentioning
confidence: 99%
“…The IMS-oaTOF MS instrument was described in detail elsewhere. ,, This instrument is equipped with an identical ion source and IMS drift tube as the standalone IMS. The ions, after passing the drift tube, penetrate through the 100 μm pinhole in the ion collector to the first chamber of a differential pumping interface.…”
Section: Methodsmentioning
confidence: 99%
“…The drift tube‐type IMS was used in the present study, [ 39–42 ] whose schematic diagram is shown in Figure 2. The IMS consisted of a CD ion source, a reaction region, an ion gate, a drift tube, and an ion collector.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used an orthogonal accelerated time‐of‐flight mass spectrometer, which was built in our laboratory. [ 40 ] Using this technique, we assign each IMS peak to the mass–charge ratios m / z and determine the possible structures of the corresponding ions, if possible. [ 41 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of most VOCs in exhaled breath is low (usually below 1 ppm), so that equipment with high sensitivity is necessary for the detection [12]. The general VOC detection methods include gas chromatography-mass spectrometry (GC-MS) [13,14], ion mobility spectrometry (IMS) [15], gold nanoparticle sensor array [16], and semiconductor metal oxide sensor [17,18]. Among them, semiconductor metal oxide sensor has a good prospect for VOC detection because of its great sensitivity, fast response, lower cost, as well as simple fabrication [19,20].…”
Section: Introduction mentioning
confidence: 99%